PEMANFAATAN CROSS CULTURAL UNDERSTANDING (PEMAHAMAN LINTAS BUDAYA) DALAM BAHAN AJAR NUSUS ADABIYYAH (ANALISIS TEKS SASTRA) - Busri, Hasan; Irawati, Retno Purnama; Nawawi, Muchlisin (Jurnal Penelitian Pendidikan, 2016)
Nusus Adabiyah (Analisis Teks Sastra) is one of the new subject in competence and conservation based curriculum in Arabian Education Department of FBS UNNES. Nusus Adabiyah (Analisis Teks Sastra) is given in 6th semester as a continuity of subject Pengantar Ilmu Sastra (1st Adab or Sejarah Sastra Arab (4th semester) and subject Tarikh semester). Nusus Adabiyah (Analisis Teks Sastra) needs to be improved through the development of lesson plan and suitable materials. The implementation of Cross Cultural Understanding (CCU) in the materials will help students in learning the literature text analysis as well as improving their awareness in culture and analysis ability. This article analyse the studentsâ need of Nusus Adabiyyah material, the studentsâ response toward Nusus Adabiyyah material and the utilization of CCU in Nusus Adabiyyah material. Research and Development Approach is used in this study while the subject of Â this study is students of Arabian Eduaction which have studied Pengantar Ilmu Sastra and Tarikh Adab or Sejarah Sastra Arab in the previous semesters. Method of collecting the data in this study includes test and and non-test methods: questionaire, interview, and documentation. 27 students (54%) need materials which focus on the Arabian literature work and its analysis technique. The other materials beside those two are not yet needed because students still have difficulties in analysing the Arabian literature work. The learning of Nusus Adabiyah by inserting CCU makes the students become more motivated to learn, to think positively, and they are also encouraged to learn Arabian culture.